Collected Works of Rev. Dr. Placid J.Podipara CMI, Vols I — V - Perumpallikunnel, Kurian (Asian Horizons, 2008)
Dr Thomas Kalayil CMI, Editor, Collected Works of Rev. Dr. Placid J. Podipara CMI, Vols I — V, Sanjos Publications/Mannanam: 2007, lix + 1119; 672; 291; 862; 188 pages.